Mathematical communication skills based on cognitive styles and gender - Kamid Kamid; M. Rusdi; Olva Fitaloka; Fibrika Rahmat Basuki; Khairul Anwar (Institute of Advanced Engineering and Science, 2020)
This research aimed to determine the differences of mathematical communication skills based on cognitive styles and gender. This research was a mixed-method with sequential explanatory design. The population was grade XI students at Senior High School in Jambi City consisting of 53 male and 72 female students. The study used a total sampling. The key informant consisted of four field independent and four field dependent. The instruments were used cognitive style test, mathematical communication test, and interviews. The differences of mathematical communication skills were analyzed using Mann-Whitney U-Test. Qualitative data were analyze descriptively using Miles and Huberman model. The results of this study showed that there was a significant difference of Field Independent (FI) and Field Dependent (FD) students in mathematical communication skills. FI can explain the information on the question well, using the mathematical model appropriately, explaining the problem-solving strategy very clear and structured, and being able to evaluate clearly and accurately. FD able to describing the information on the matter, but less complete, using the mathematical model appropriately, explaining the problem-solving strategy, but less complete, and being able to evaluate it quite clearly. The mathematical communication skills of male and female students were not significant differences. Male students are able to explain the strategy and the steps of solving the problem quite clearly, but less structured. Female students are able to explain the strategy and steps to resolve the problem clearly and structured.